Preparation method of nano photovoltaic glass for solar cell

By preparing nano -boiled glass light glass on the glass battery, and covering the porous structure and photocatalytic active materials, the problem of reduced power generation efficiency caused by pollutant obstruction, realizing the high scratch and self -cleaning performance of the glass, extending the equipment, extending the equipment Life life.

CN119349896APending Publication Date: 2025-01-24JIANGSU SIMBA NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411493207.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing glass for solar cells is easily blocked by pollutants after long-term use outdoors, affecting power generation efficiency, and low manual cleaning efficiency, resulting in huge losses.

Method used

The amygenic oscillating of the amproofed body is used as an active adhesive, and the coating solution is made with isopropyl aluminum, orthopedic silicate ethyl, and tetrachide ammonium oxide. And on its surface covering porous structure and photocatalytic activity materials to improve its self -cleaning performance.

Benefits of technology

The scratch resistance and self-cleaning performance of nano-photovoltaic glass for solar cells are improved, the adhesion of pollutants is reduced, the service life of the photovoltaic power station is extended and the power generation efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005100608540000091
    Figure BDA0005100608540000091
Patent Text Reader

Abstract

The invention discloses a preparation method of nano photovoltaic glass for a solar cell, and relates to the technical field of glass. When the nano photovoltaic glass for the solar cell is prepared, aluminum isopropoxide is used as an aluminum source, tetraethoxysilane is used as a silicon source, tetraethylammonium hydroxide is used as a template agent, and zeolite precursor sol is prepared through vacuum evaporation; zeolite precursor sol is used as an active adhesive, the zeolite precursor sol, aluminum isopropoxide, tetraethoxysilane and tetraethylammonium hydroxide are prepared into a film coating solution, and a dipping-pulling method and a vapor phase inversion method are adopted to prepare the nano zeolite photovoltaic glass. Preparing bismuth oxychloride, methacrylic acid, dimethylaminoethyl methacrylate and ammonium persulfate into a post-treatment solution; and coating the nano zeolite photovoltaic glass with the post-treatment solution by adopting a dipping-pulling method, and drying and curing to obtain the nano photovoltaic glass for the solar cell. The prepared nano photovoltaic glass for the solar cell has excellent scratch resistance and self-cleaning performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass, and in particular to a method for preparing nano photovoltaic glass for solar cells. Background Art

[0002] As the energy and environmental crisis becomes increasingly serious, solar cells have come into being. With the development of the global photovoltaic industry, solar power stations have been built in many places in the world. As one of the important components of silicon solar modules, solar cell cover glass usually refers to the glass covering the silicon wafer of solar cells. It does not affect the performance of solar cells and has many advantages, such as protecting the silicon wafer from dust, mechanical wear and impact, and harsh environment. Because power stations mainly work outdoors, the surface of photovoltaic panels will inevitably be blocked by pollutants over time, which greatly affects the power generation efficiency of the power station and causes huge losses. For these pollutants, if you choose to clean them manually, it will not only waste a lot of manpower and material resources, but the effect is not ideal. Therefore, it is very necessary to develop nano photovoltaic glass for solar cells with self-cleaning properties. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing nano photovoltaic glass for solar cells to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] A method for preparing nano photovoltaic glass for solar cells, the method comprising: using zeolite precursor sol as an active adhesive, preparing a coating solution with aluminum isopropoxide, ethyl orthosilicate, and tetraethylammonium hydroxide, and preparing nano zeolite photovoltaic glass by an immersion-pulling method and a vapor phase inversion method; and then coating the post-treatment solution on the nano zeolite photovoltaic glass by an immersion-pulling method, and preparing the nano photovoltaic glass for solar cells after drying and curing.

[0006] The zeolite precursor sol is prepared by vacuum evaporation using aluminum isopropoxide as an aluminum source, ethyl orthosilicate as a silicon source, and tetraethylammonium hydroxide as a template agent;

[0007] The post-treatment solution is prepared by mixing bismuth oxychloride, methacrylic acid, dimethylaminoethyl methacrylate and ammonium persulfate.

[0008] As an optimization, the method for preparing the nano photovoltaic glass for solar cells includes the following preparation steps:

[0009] (1) mixing aluminum isopropoxide solution and ethyl orthosilicate solution in a mass ratio of 1:(6-7) and stirring at 40-50° C. and 300-500 r / min for 8-10 hours under vacuum conditions to obtain a zeolite precursor sol;

[0010] (2) mixing zeolite aggregate sol, zeolite precursor sol, Tween-20, and anhydrous ethanol in a mass ratio of 1:(0.4-0.5):(0.04-0.06):(20-30) to obtain a coating solution; immersing ultra-white glass in the coating solution, allowing it to stand for 10-12 minutes, extracting the ultra-white glass at a speed of 58-62 mm / min, placing it in a stainless steel autoclave, adding 5% deionized water by volume of the stainless steel autoclave, and steam crystallizing it at 136-140° C. under vacuum conditions for 3-4 hours, taking it out, placing it in a muffle furnace for high-temperature tempering, cooling it to room temperature, and then taking it out to obtain nano-zeolite photovoltaic glass;

[0011] (3) Immersing the nano-zeolite photovoltaic glass in the post-treatment solution, standing for 2 to 3 minutes, extracting the nano-zeolite photovoltaic glass at a speed of 190 to 210 μm / s, and drying at 80 to 90° C. for 8 to 10 hours to obtain the nano-zeolite photovoltaic glass for solar cells.

[0012] As an optimization, the preparation method of the aluminum isopropoxide solution in step (1) is: aluminum isopropoxide and a tetraethylammonium hydroxide aqueous solution with a mass fraction of 30% to 40% are mixed uniformly in a mass ratio of 1:(9 to 10), and stirred at 10 to 30° C. and 300 to 500 r / min for 2 to 3 hours to prepare the aluminum isopropoxide solution.

[0013] As an optimization, the preparation method of the tetraethyl orthosilicate solution in step (1) is: mix tetraethyl orthosilicate, a tetraethylammonium hydroxide aqueous solution with a mass fraction of 30% to 40%, and deionized water in a mass ratio of 1: (0.3 to 0.4): (1.5 to 1.7), stir at 10 to 30° C. and 300 to 500 r / min for 2 to 3 hours to prepare the tetraethyl orthosilicate solution.

[0014] As an optimization, the preparation method of the zeolite aggregate sol in step (2) is: mix tetraethyl orthosilicate, aluminum isopropoxide, a tetraethylammonium hydroxide aqueous solution with a mass fraction of 30% to 40%, and anhydrous ethanol in a mass ratio of 1: (0.03 to 0.04): (0.7 to 0.8): (2 to 3), and stir at 100 to 110° C. and 300 to 500 r / min for 8 to 10 hours to obtain a zeolite aggregate sol.

[0015] As an optimization, the thickness of the ultra-white glass in step (2) is 3 mm.

[0016] As an optimization, the process parameters of the high temperature tempering in step (2) are: heating to 100°C at a rate of 10°C / min and keeping warm for 8 to 10 minutes, then heating to 550°C at a heating rate of 20°C / min and keeping warm for 8 to 10 minutes.

[0017] As an optimization, the preparation method of the post-treatment solution in step (3) is as follows: bismuth oxychloride and butyl acetate are mixed evenly in a mass ratio of 1: (50-60), ultrasonically dispersed for 20-30 minutes, methacrylic acid 7-8 times the mass of bismuth oxychloride and dimethylaminoethyl methacrylate 3-4 times the mass of bismuth oxychloride are added and mixed evenly, stirred at 10-30° C. and 300-500 r / min for 2-3 hours, and ammonium persulfate 0.04-0.06 mass of methacrylic acid is added, mixed evenly, and prepared into a post-treatment solution.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] When preparing nano photovoltaic glass for solar cells, the present invention uses aluminum isopropoxide as an aluminum source, ethyl orthosilicate as a silicon source, and tetraethyl ammonium hydroxide as a template agent to obtain a zeolite precursor sol by vacuum evaporation; uses the zeolite precursor sol as an active adhesive to prepare a coating solution with aluminum isopropoxide, ethyl orthosilicate, and tetraethyl ammonium hydroxide, and adopts an immersion-pulling method and a vapor phase inversion method to obtain the nano zeolite photovoltaic glass; bismuth oxychloride, methacrylic acid, dimethylaminoethyl methacrylate, and ammonium persulfate are prepared into a post-treatment solution; adopts an immersion-pulling method to coat the post-treatment solution on the nano zeolite photovoltaic glass, and obtains the nano photovoltaic glass for solar cells after drying and solidification.

[0020] First, a zeolite precursor sol is prepared by vacuum evaporation using aluminum isopropoxide as an aluminum source, tetraethyl orthosilicate as a silicon source, and tetraethyl ammonium hydroxide as a template agent; the zeolite precursor sol is used as an active adhesive to prepare a coating solution with aluminum isopropoxide, tetraethyl orthosilicate, and tetraethyl ammonium hydroxide, and a nano-zeolite photovoltaic glass is prepared by an immersion-pulling method and a vapor phase inversion method; covering the surface of photovoltaic glass with a layer of porous silica film is a common method for reducing the reflectivity of photovoltaic glass, but the mechanical properties of this amorphous porous silica are poor, and a zeolite aggregate sol is used as a structure provider, and a zeolite precursor sol is used as a reactive adhesive, and a nano-zeolite photovoltaic glass is prepared by an immersion-pulling method and a vapor phase inversion method; zeolite is a microporous aluminosilicate crystalline material, which replaces amorphous silica prepared by traditional processes, can significantly improve the mechanical strength and pencil hardness of the film layer, and endow the nano-photovoltaic glass for solar cells with excellent scratch resistance.

[0021] Secondly, bismuth oxychloride, methacrylic acid, dimethylaminoethyl methacrylate and ammonium persulfate are prepared into a post-treatment solution; the post-treatment solution is coated on the nano zeolite photovoltaic glass by an immersion-pulling method, and the nano photovoltaic glass for solar cells is obtained after drying and solidification; bismuth oxychloride has photocatalytic activity and can catalytically degrade organic pollutants attached to the photovoltaic glass under light, giving the nano photovoltaic glass for solar cells excellent self-cleaning properties; methacrylic acid and dimethylaminoethyl methacrylate are polymerized under the action of an initiator to form a copolymer attached to the surface of the photovoltaic glass, thereby improving the hydrophilicity of the photovoltaic glass and allowing rainwater to form a water film on the surface of the photovoltaic glass, and the pollutants are carried away by the water film, thereby achieving a self-cleaning effect. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Embodiment 1:

[0024] A method for preparing nano photovoltaic glass for solar cells, the method for preparing nano photovoltaic glass for solar cells comprising the following preparation steps:

[0025] (1) Aluminum isopropoxide and a 30% aqueous solution of tetraethylammonium hydroxide by mass fraction were mixed uniformly in a mass ratio of 1:9, and stirred at 10°C and 300 r / min for 3 h to prepare an aluminum isopropoxide solution; ethyl orthosilicate, a 30% aqueous solution of tetraethylammonium hydroxide by mass fraction, and deionized water were mixed uniformly in a mass ratio of 1:0.3:1.5, and stirred at 10°C and 300 r / min for 3 h to prepare an ethyl orthosilicate solution; aluminum isopropoxide solution and ethyl orthosilicate solution were mixed uniformly in a mass ratio of 1:6, and stirred at 40°C and 300 r / min for 10 h under vacuum conditions to prepare a zeolite precursor sol;

[0026] (2) Tetraethyl orthosilicate, aluminum isopropoxide, 30% tetraethylammonium hydroxide aqueous solution, and anhydrous ethanol are mixed uniformly in a mass ratio of 1:0.03:0.7:2, and stirred at 100°C and 300 r / min for 10 h to obtain a zeolite aggregate sol; the zeolite aggregate sol, zeolite precursor sol, Tween-20, and anhydrous ethanol are mixed uniformly in a mass ratio of 1:0.4:0.04:20 to obtain a coating solution; and ultra-white glass is immersed in the coating solution. The ultra-white glass was extracted at a speed of 58 mm / min, placed in a stainless steel autoclave, and 5% of the volume of the stainless steel autoclave was added with deionized water. Under vacuum conditions, the mixture was steam crystallized at 136°C for 4 hours. The mixture was taken out and placed in a muffle furnace. The mixture was heated to 100°C at a speed of 10°C / min and kept warm for 8 minutes. The mixture was then heated to 550°C at a heating rate of 20°C / min and kept warm for 8 minutes. The mixture was cooled to room temperature and then taken out to obtain nano-zeolite photovoltaic glass.

[0027] (3) Bismuth oxychloride and butyl acetate were mixed at a mass ratio of 1:50, ultrasonically dispersed for 20 minutes, methacrylic acid (7 times the mass of bismuth oxychloride) and dimethylaminoethyl methacrylate (3 times the mass of bismuth oxychloride) were added and mixed evenly, stirred at 10° C. and 300 r / min for 3 hours, and ammonium persulfate (0.04 mass of methacrylic acid) was added and mixed evenly to prepare a post-treatment solution; the nano-zeolite photovoltaic glass was immersed in the post-treatment solution, allowed to stand for 2 minutes, extracted at a speed of 190 μm / s, and dried at 80° C. for 10 hours to obtain nano-photovoltaic glass for solar cells.

[0028] Embodiment 2:

[0029] A method for preparing nano photovoltaic glass for solar cells, the method for preparing nano photovoltaic glass for solar cells comprising the following preparation steps:

[0030] (1) Aluminum isopropoxide and a 35% aqueous solution of tetraethylammonium hydroxide by mass fraction were mixed uniformly in a mass ratio of 1:9.5, and stirred at 20°C and 400 r / min for 2.5 h to prepare an aluminum isopropoxide solution; ethyl orthosilicate, a 35% aqueous solution of tetraethylammonium hydroxide by mass fraction, and deionized water were mixed uniformly in a mass ratio of 1:0.35:1.6, and stirred at 20°C and 400 r / min for 2.5 h to prepare an ethyl orthosilicate solution; aluminum isopropoxide solution and ethyl orthosilicate solution were mixed uniformly in a mass ratio of 1:6.5, and stirred at 45°C and 400 r / min for 9 h under vacuum conditions to prepare a zeolite precursor sol;

[0031] (2) Tetraethyl orthosilicate, aluminum isopropoxide, 35% tetraethylammonium hydroxide aqueous solution, and anhydrous ethanol were mixed in a mass ratio of 1:0.035:0.75:2.5, and stirred at 105°C and 400 r / min for 9 hours to obtain a zeolite aggregate sol; the zeolite aggregate sol, zeolite precursor sol, Tween-20, and anhydrous ethanol were mixed in a mass ratio of 1:0.45:0.05:25 to obtain a coating solution; and ultra-white glass was immersed in the coating solution. The ultra-white glass was extracted at a speed of 60 mm / min and placed in a stainless steel autoclave. Deionized water (5% of the volume of the stainless steel autoclave) was added and steam crystallized at 138°C for 3.5 hours under vacuum conditions. The glass was taken out and placed in a muffle furnace. The glass was heated to 100°C at a speed of 10°C / min and kept warm for 9 minutes. The glass was then heated to 550°C at a heating rate of 20°C / min and kept warm for 9 minutes. The glass was cooled to room temperature and then taken out to obtain nano-zeolite photovoltaic glass.

[0032] (3) Bismuth oxychloride and butyl acetate were mixed at a mass ratio of 1:55, ultrasonically dispersed for 25 minutes, methacrylic acid (7.5 times the mass of bismuth oxychloride) and dimethylaminoethyl methacrylate (3.5 times the mass of bismuth oxychloride) were added and mixed evenly, stirred at 20°C and 400 r / min for 2.5 hours, ammonium persulfate (0.05 mass of methacrylic acid) was added, mixed evenly, and a post-treatment solution was prepared; the nano-zeolite photovoltaic glass was immersed in the post-treatment solution, allowed to stand for 2.5 minutes, the nano-zeolite photovoltaic glass was extracted at a speed of 200 μm / s, and dried at 85°C for 9 hours to obtain nano-photovoltaic glass for solar cells.

[0033] Embodiment 3:

[0034] A method for preparing nano photovoltaic glass for solar cells, the method for preparing nano photovoltaic glass for solar cells comprising the following preparation steps:

[0035] (1) Aluminum isopropoxide and a 40% aqueous solution of tetraethylammonium hydroxide by mass fraction were mixed uniformly in a mass ratio of 1:10, and stirred at 30°C and 500 r / min for 2 h to prepare an aluminum isopropoxide solution; ethyl orthosilicate, a 40% aqueous solution of tetraethylammonium hydroxide by mass fraction, and deionized water were mixed uniformly in a mass ratio of 1:0.4:1.7, and stirred at 30°C and 500 r / min for 2 h to prepare an ethyl orthosilicate solution; aluminum isopropoxide solution and ethyl orthosilicate solution were mixed uniformly in a mass ratio of 1:7, and stirred at 50°C and 500 r / min for 8 h under vacuum conditions to prepare a zeolite precursor sol;

[0036] (2) Tetraethyl orthosilicate, aluminum isopropoxide, 40% tetraethylammonium hydroxide aqueous solution, and anhydrous ethanol are mixed uniformly in a mass ratio of 1:0.04:0.8:3, and stirred at 110° C. and 500 r / min for 8 h to obtain a zeolite aggregate sol; the zeolite aggregate sol, zeolite precursor sol, Tween-20, and anhydrous ethanol are mixed uniformly in a mass ratio of 1:0.5:0.06:30 to obtain a coating solution; and ultra-white glass is immersed in the coating solution. After standing for 10 minutes, the ultra-white glass was extracted at a speed of 62 mm / min, placed in a stainless steel autoclave, and deionized water of 5% of the volume of the stainless steel autoclave was added. Under vacuum conditions, the mixture was steam crystallized at 140°C for 3 hours. The mixture was taken out and placed in a muffle furnace. The mixture was heated to 100°C at a speed of 10°C / min and kept warm for 10 minutes. The mixture was then heated to 550°C at a heating rate of 20°C / min and kept warm for 10 minutes. The mixture was cooled to room temperature and then taken out to obtain nano-zeolite photovoltaic glass.

[0037] (3) Bismuth oxychloride and butyl acetate were mixed at a mass ratio of 1:60, ultrasonically dispersed for 30 minutes, methacrylic acid 8 times the mass of bismuth oxychloride and dimethylaminoethyl methacrylate 4 times the mass of bismuth oxychloride were added and mixed evenly, stirred at 30°C and 500 r / min for 2 hours, and ammonium persulfate 0.06 mass of methacrylic acid was added and mixed evenly to prepare a post-treatment solution; the nano-zeolite photovoltaic glass was immersed in the post-treatment solution, allowed to stand for 3 minutes, the nano-zeolite photovoltaic glass was extracted at a speed of 210 μm / s, and dried at 90°C for 8 hours to obtain nano-photovoltaic glass for solar cells.

[0038] Comparative Example 1:

[0039] The difference between the preparation method of nano photovoltaic glass for solar cells in Comparative Example 1 and Example 2 is that step (1) and step (2) are not performed, and step (3) is modified as follows: tetraethyl orthosilicate, ethanol, ammonia, deionized water, and polyethylene glycol with a mass fraction of 200 are mixed uniformly in a mass ratio of 1:34.2:0.7:2:0.08, stirred at 5°C and 400r / min for 5h, and aged at 30°C for 3 days to obtain a coating solution; ultra-white glass is immersed in the coating solution, allowed to stand for 10min, the ultra-white glass is extracted at a speed of 62mm / min, taken out, dried at 100°C for 5h, placed in a muffle furnace, heated to 100°C at a speed of 10°C / min and kept warm for 10min, and then heated at a heating rate of 20°C / min. The temperature was raised to 550°C and kept warm for 10 minutes, and then taken out after cooling to room temperature to obtain nano-silicon dioxide photovoltaic glass; bismuth oxychloride and butyl acetate were mixed evenly at a mass ratio of 1:55, ultrasonically dispersed for 25 minutes, 7.5 times the mass of bismuth oxychloride and 3.5 times the mass of dimethylaminoethyl methacrylate were added and mixed evenly, stirred at 20°C and 400r / min for 2.5 hours, 0.05 ammonium persulfate of methacrylic acid was added, mixed evenly, and prepared into a post-treatment solution; the nano-silicon dioxide photovoltaic glass was immersed in the post-treatment solution, allowed to stand for 2.5 minutes, the nano-silicon dioxide photovoltaic glass was extracted at a speed of 200μm / s, and dried at 85°C for 9 hours to obtain nano-photovoltaic glass for solar cells. The remaining steps are the same as in Example 2.

[0040] Comparative Example 2:

[0041] The preparation method of the nano photovoltaic glass for solar cells in Comparative Example 2 is different from that in Example 2 in step (3), where step (3) is modified as follows: methacrylic acid, dimethylaminoethyl methacrylate, and butyl acetate are mixed uniformly in a mass ratio of 1:0.28:4.4, stirred at 20°C and 400r / min for 2.5h, 0.05% ammonium persulfate by mass of methacrylic acid is added, mixed uniformly, and a post-treatment solution is prepared; the nano zeolite photovoltaic glass is immersed in the post-treatment solution, allowed to stand for 2.5min, the nano zeolite photovoltaic glass is extracted at a speed of 200μm / s, and dried at 85°C for 9h to obtain the nano photovoltaic glass for solar cells. The remaining steps are the same as those in Example 2.

[0042] Comparative Example 3:

[0043] The preparation method of nano photovoltaic glass for solar cells in Comparative Example 3 is different from that in Example 2 only in that step (3) is not performed, and step (2) is modified as follows: tetraethyl orthosilicate, aluminum isopropoxide, a 35% tetraethylammonium hydroxide aqueous solution, and anhydrous ethanol are uniformly mixed in a mass ratio of 1:0.035:0.75:2.5, and stirred at 105°C and 400r / min for 9h to obtain a zeolite aggregate sol; the zeolite aggregate sol, zeolite precursor sol, Tween-20, and anhydrous ethanol are uniformly mixed in a mass ratio of 1:0.45:0.05:2.5. 5. Mix evenly to obtain a coating solution; immerse the ultra-white glass in the coating solution, let it stand for 11 minutes, extract the ultra-white glass at a speed of 60 mm / min, place it in a stainless steel autoclave, add 5% deionized water by volume of the stainless steel autoclave, steam crystallize it at 138°C for 3.5 hours under vacuum conditions, take it out, place it in a muffle furnace, heat it to 100°C at a speed of 10°C / min and keep it warm for 9 minutes, then heat it to 550°C at a heating rate of 20°C / min and keep it warm for 9 minutes, cool it to room temperature and take it out to obtain nano photovoltaic glass for solar cells. The remaining steps are the same as in Example 2.

[0044] Test Example 1

[0045] Scratch resistance test

[0046] Test method: According to the requirements of GB / T6739, the pencil hardness of the examples and comparative examples was tested using an OHO-A pencil hardness tester. The results are shown in Table 1.

[0047] Table 1

[0048] Pencil hardness Pencil hardness Example 1 5H Comparative Example 1 3H Example 2 6H Comparative Example 2 5H Example 3 6H Comparative Example 3 5H

[0049] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the nano photovoltaic glass for solar cells prepared by the present invention has good scratch resistance.

[0050] By comparison, the pencil hardness of Examples 1 to 3 is greater than that of Comparative Example 1, indicating that the zeolite precursor sol is prepared by vacuum evaporation using aluminum isopropoxide as the aluminum source, tetraethyl orthosilicate as the silicon source, and tetraethyl ammonium hydroxide as the template agent; the zeolite precursor sol is used as the active adhesive, and is prepared into a coating solution with aluminum isopropoxide, tetraethyl orthosilicate, and tetraethyl ammonium hydroxide, and the nano zeolite photovoltaic glass is prepared by the immersion-pulling method and the vapor phase inversion method; covering the surface of photovoltaic glass with a layer of porous silica film is a common method for reducing the reflectivity of photovoltaic glass, but the mechanical properties of this amorphous porous silica are poor, and the nano zeolite photovoltaic glass is prepared by the immersion-pulling method and the vapor phase inversion method using the zeolite aggregate sol as the structure provider and the zeolite precursor sol as the reactive adhesive; zeolite is a microporous aluminosilicate crystalline material, which replaces the amorphous silica prepared by the traditional process, and can significantly improve the mechanical strength and pencil hardness of the film layer, giving the nano photovoltaic glass for solar cells excellent scratch resistance.

[0051] Test Example 2

[0052] Self-cleaning performance test

[0053] Photocatalytic self-cleaning test method: Using 20 mg / L methyl orange aqueous solution as the pollutant, a mercury lamp was used to simulate natural light, the absorbance of the sample was measured by spectrophotometer, and the degradation efficiency of methyl orange in the embodiment and comparative example over 24 hours was calculated.

[0054] Hydrophilic self-cleaning test method: The water drop contact angle of the embodiment and the comparative example was tested using the sessile drop method on an OCA20 contact angle meter, and the water drop volume was 5 μL. The results are shown in Table 2.

[0055] Table 2

[0056]

[0057] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 2, it can be found that the nano photovoltaic glass for solar cells prepared by the present invention has good self-cleaning performance.

[0058] By comparison, the degradation rate of methyl orange in Examples 1 to 3 is greater than the degradation rate of methyl orange in Comparative Examples 2 to 3, indicating that bismuth oxychloride, methacrylic acid, dimethylaminoethyl methacrylate, and ammonium persulfate are prepared into a post-treatment solution; the post-treatment solution is coated on the nano zeolite photovoltaic glass by an immersion-pulling method, and the nano photovoltaic glass for solar cells is obtained after drying and curing; bismuth oxychloride has photocatalytic activity and can catalytically degrade organic pollutants attached to the photovoltaic glass under light, thereby giving the nano photovoltaic glass for solar cells excellent self-cleaning properties.

[0059] By comparison, the contact angles of Examples 1 to 3 are smaller than that of Comparative Example 3, indicating that bismuth oxychloride, methacrylic acid, dimethylaminoethyl methacrylate, and ammonium persulfate are prepared into a post-treatment solution; the post-treatment solution is coated on the nano-zeolite photovoltaic glass by the immersion-pulling method, and the nano-photovoltaic glass for solar cells is obtained after drying and curing; methacrylic acid and dimethylaminoethyl methacrylate are polymerized under the action of an initiator to form a copolymer attached to the surface of the photovoltaic glass, thereby improving the hydrophilicity of the photovoltaic glass, so that rainwater can form a water film on the surface of the photovoltaic glass, and the pollutants are carried away by the water film, thereby achieving a self-cleaning effect.

[0060] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing nano photovoltaic glass for solar cells, characterized in that: The preparation method of the nano photovoltaic glass for solar cells is to use zeolite precursor sol as an active binder, prepare a coating solution with aluminum isopropoxide, ethyl orthosilicate, and tetraethylammonium hydroxide, and adopt an immersion-pulling method and a vapor phase inversion method to prepare the nano zeolite photovoltaic glass; then adopt an immersion-pulling method to coat the post-treatment solution on the nano zeolite photovoltaic glass, and after drying and curing, prepare the nano photovoltaic glass for solar cells; The zeolite precursor sol is prepared by vacuum evaporation using aluminum isopropoxide as an aluminum source, ethyl orthosilicate as a silicon source, and tetraethylammonium hydroxide as a template agent; The post-treatment solution is prepared by mixing bismuth oxychloride, methacrylic acid, dimethylaminoethyl methacrylate and ammonium persulfate.

2. The method for preparing nano photovoltaic glass for solar cells according to claim 1, characterized in that: The method for preparing the nano photovoltaic glass for solar cells comprises the following preparation steps: (1) mixing aluminum isopropoxide solution and ethyl orthosilicate solution in a mass ratio of 1:(6-7) and stirring at 40-50° C. and 300-500 r / min for 8-10 hours under vacuum conditions to obtain a zeolite precursor sol; (2) mixing zeolite aggregate sol, zeolite precursor sol, Tween-20, and anhydrous ethanol in a mass ratio of 1:(0.4-0.5):(0.04-0.06):(20-30) to obtain a coating solution; immersing ultra-white glass in the coating solution, allowing it to stand for 10-12 minutes, extracting the ultra-white glass at a speed of 58-62 mm / min, placing it in a stainless steel autoclave, adding 5% deionized water by volume of the stainless steel autoclave, and steam crystallizing it at 136-140° C. under vacuum conditions for 3-4 hours, taking it out, placing it in a muffle furnace for high-temperature tempering, cooling it to room temperature, and then taking it out to obtain nano-zeolite photovoltaic glass; (3) Immersing the nano-zeolite photovoltaic glass in the post-treatment solution, standing for 2 to 3 minutes, extracting the nano-zeolite photovoltaic glass at a speed of 190 to 210 μm / s, and drying at 80 to 90° C. for 8 to 10 hours to obtain the nano-zeolite photovoltaic glass for solar cells.

3. The method for preparing nano photovoltaic glass for solar cells according to claim 2, characterized in that: The preparation method of the aluminum isopropoxide solution in step (1) is as follows: aluminum isopropoxide and a tetraethylammonium hydroxide aqueous solution with a mass fraction of 30% to 40% are uniformly mixed in a mass ratio of 1:(9 to 10), and stirred at 10 to 30° C. and 300 to 500 r / min for 2 to 3 hours to prepare the aluminum isopropoxide solution.

4. The method for preparing nano photovoltaic glass for solar cells according to claim 2, characterized in that: The preparation method of the tetraethyl orthosilicate solution in step (1) is as follows: tetraethyl orthosilicate, a tetraethylammonium hydroxide aqueous solution with a mass fraction of 30% to 40%, and deionized water are uniformly mixed in a mass ratio of 1: (0.3 to 0.4): (1.5 to 1.7), and stirred at 10 to 30° C. and 300 to 500 r / min for 2 to 3 hours to prepare the tetraethyl orthosilicate solution.

5. The method for preparing nano photovoltaic glass for solar cells according to claim 2, characterized in that: The preparation method of the zeolite aggregate sol in step (2) is as follows: tetraethyl orthosilicate, aluminum isopropoxide, a 30% to 40% tetraethylammonium hydroxide aqueous solution, and anhydrous ethanol are uniformly mixed in a mass ratio of 1:(0.03 to 0.04):(0.7 to 0.8):(2 to 3), and stirred at 100 to 110° C. and 300 to 500 r / min for 8 to 10 hours to obtain a zeolite aggregate sol.

6. The method for preparing nano photovoltaic glass for solar cells according to claim 2, characterized in that: The thickness of the ultra-white glass in step (2) is 3 mm.

7. The method for preparing nano photovoltaic glass for solar cells according to claim 2, characterized in that: The process parameters of the high temperature tempering in step (2) are: heating to 100°C at a rate of 10°C / min and keeping warm for 8 to 10 minutes, then heating to 550°C at a heating rate of 20°C / min and keeping warm for 8 to 10 minutes.

8. The method for preparing nano photovoltaic glass for solar cells according to claim 2, characterized in that: The preparation method of the post-treatment solution in step (3) is as follows: bismuth oxychloride and butyl acetate are mixed uniformly in a mass ratio of 1: (50-60), ultrasonically dispersed for 20-30 minutes, methacrylic acid 7-8 times the mass of bismuth oxychloride and dimethylaminoethyl methacrylate 3-4 times the mass of bismuth oxychloride are added and mixed uniformly, stirred at 10-30° C. and 300-500 r / min for 2-3 hours, and ammonium persulfate 0.04-0.06 mass of methacrylic acid is added, mixed uniformly, and prepared into a post-treatment solution.